Strategi Pemerintah Daerah Terhadap Pengentasan Kemiskinan di Kabupaten Sidenreng Rappang - Lutfiah Asilah M; Erfina Erfina; Muhammad Ikbal (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to analyze the local government’s strategy for poverty alleviation in Sidenreng Rappang Regency. The research employed a descriptive quantitative approach involving 100 respondents selected through random sampling. Data were collected through observation, questionnaires, and literature review, and were analyzed using simple linear regression with the assistance of IBM SPSS version 26. The findings indicate that the government’s strategy has a strong and significant influence on poverty alleviation, contributing 95.5% to the reduction of poverty levels. This result demonstrates that the policies and programs implemented by the local government have been effective and have produced tangible impacts in reducing poverty at the community level. In substantive terms, the rejection of the null hypothesis confirms that well-planned and properly implemented government strategies directly enhance community welfare and accelerate poverty reduction outcomes. Furthermore, several key factors were identified as supporting the effectiveness of these strategies, including environmental conditions (25%), human resource quality (21%), and leadership (24%), with an overall average achievement categorized as good (70%).